EFEK PEMBERIAN PUPUK HAYATI KONSORSIUM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SAWI (Brassica juncea L.) - A. Marthin Kalay; Reginawanti Hindersah (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2016)
Fertilizer is one of the important limited factor in plant cultivation system. Biofertilizer is a kind of fertilizer which improve nutrient availability in soil and subsequently plant yield. A research was carried out in village Waiheru, District Baguala, Ambon to determine the effect of different level of mixed biofertilizer on the growth and yield of caisim that grown on Alluvial. The research used Randomized Completely Block Design (RCBD) with three concentration of liquid biofertilizer, namely: 0.1%, 0.5% and 1%. Treatment control was without biofertilizer. The results showed that inoculation of liquid biological fertilizer at concentration of 1% improved growth and yield of caisim higher than the concentration of 0.1% and 0.5%. Inoculation of 1% biofertilizer increased the fresh weight of caisim shoot up to 37.36% compared to that of controls. While, fresh weight of caisim with biofertilizer of 0.1% and 0.5% was 24.52% and 28.94% respectively.Keyword: Ambon, Mixed Biofertilizer, Caisim